ANALISIS PERILAKU KESEHATAN DALAM KETAATAN BERIBADAH WARGA MUHAMMADIYAH DITENGAH PANDEMI COVID-19 - Ida Untari; Suyanto Suyanto; Wijayanti Wijayanti (Jurnal Surya Muda, 2022)
The Covid-19 outbreak has made major changes in all orders of human life, including changes in the order of human life, from relationships to fellow humans and human relationships to God. This study aims to analyze health behavior in the worship of Muhammadiyah residents in the midst of the Covid-19 pandemic. The research method is in the form of a descriptive survey through a questionnaire in the form of a google form that is distributed via whatsapp during November - December 2020 evenly at seven Muhammadiyah branches in Surakarta City by getting 84 active residents. The analysis used univariate, crosstab and binary logistic regression at 5% significance. Knowledge and obstacles are the most influential factors in worshiping in the midst of the Covid-19 Pandemic. The biggest obstacle is the belief that going to the mosque in congregation is the fulfillment of Muslim obligations (p: 0.014).